Mario Bellatin y las formas de la escritura - Jaimes, Hector, 1964- (Book collections on Project MUSE., 2020)
"This book brings together the collaboration of three important writers, as well as that of sixteen leading researchers, around the work of Mexican writer Mario Bellatin. With a varied and multidisciplinary critical approach, each section of the book highlights the different thematic axes that arise from the same work of this writer; namely: transliterature, philosophy, body, humor, gender and aesthetics. In addition, the book has the collaboration of Mario Bellatin himself, who participates with an unpublished text. In short, it is an important critical contribution on the work of one of the most sui generis contemporary writers of the moment"--